Home networking with Universal Plug and Play. - Miller, B.A (IEEE Communications magazine)
We present an overview of the Universal Plug and Play (UPnPTM ) technology and the UPnP Forum, the multicompany organization that develops parts of the architecture. A technical description of the technology is presented, followed by three illustrative usage cases where it could be applied in home networking environments. Finally, the authors describe the benefits UPnP technology can provide in home networking and discuss potential future work in this area